The Relationship of Sleep Quality to Nurses' Response Time - Kolopita, Anata Resti; Gaib, Juritno Harmi; Patonengan, Gita Sandy (Omni Health Journal, 2025)
Background: Emergency services involve rapid assessment, stabilization, and treatment of life-threatening conditions that require immediate attention. Recent studies highlight alarming increases in hospital mortality, particularly in the Emergency Department (ED), with the main causes including severe brain injury, meningitis, heart disease, trauma, kidney disease, and sepsis. Factors such as response time significantly affect patient outcomes. Objective: The purpose of this study is to determine the relationship between sleep quality and nurse response time Methods: This study adopts a cross-sectional descriptive analytical approach. Results: It was found that there was a relationship between sleep quality and response time of nurses in emergency rooms. Conclusion: Based on the results of statistical analysis,  it is obtained with a value value p = 0.003 where 0.003 is smaller than the value of α = 0.05 thus, it can be said that Ha is accepted and H0 is rejected.